23 ISO-OSMOLAR CONTRAST INDUCED HEMOLYSIS AND ACUTE CHEST SYNDROME IN A PATIENT WITH HEMOGLOBIN SC DISEASE FOLLOWING PERCUTANEOUS CORONARY INTERVENTION. (1st January 2005) - Agarwal, P. K.; Jain, N.
Abstract : A 37 year old African American woman with a medical history of hemoglobin SC disease (without prior sickling crisis), hypertension, and smoking was admitted with acute onset chest pain. The admission ECG was diagnostic of acute inferior myocardial infarction. An emergent percutaneous coronary intervention of the right coronary artery was performed successfully, during which 270 mL of iopamidol (osmolality 300) contrast was administered. On hospital day 3, patient became febrile to 101.6°F, associated with leukocytosis (49.4 K) and a 2.2 g/dL drop in hemoglobin to 9.1 g/dL. Chest radiograph revealed diffuse infiltrates. The peripheral blood smear showed both target and sickle cells. Hemoglobin electrophoresis confirmed the diagnosis of HB SC disease (HB S 55% and HB C 45%). Pancultures were negative. CT scan of brain demonstrated multiple infarcts. Exchange transfusion was done and patient improved gradually. Hemoglobin SC is a milder disease in comparison to sickle cell anemia and often patients are asymptomatic. HB C causes intracellular dehydration and this in turn leads to polymerization of HB S. On review of the literature, there are occasional case reports of hemolysis and acute chest syndrome in patients with hemoglobin SC disease following hyper-osmolar contrast administration. This is the first case report of iso-osmolar contrast induced complications in a patient with HB SC disease. This case emphasizes the importance of careful monitoring for adverse effects in patients undergoing cardiac catheterization, particularly those at high risk.